Metal Fractionation and Leaching in Soils from a Gold Mining Area in the Equatorial Rainforest Zone - Lilian Sarpong; Nathaniel Owusu Boadi; Osei Akoto (Journal of Chemistry)
In this article, a modified BCR procedure and a column leaching test were used to examine the bioavailability and mobility of heavy metals in soils collected from a gold mining area in Ghana. The results for the fractionation of Cd, Cr, Fe, and Mn indicated that high percentages of metals were found in the residual fraction. This implies that the concentrations of metals in the soil are stable under normal environmental conditions. The bioavailability of metals in the soils declined in the following order: Mn (92.4%) > Cd (64.6%) > Cr (46.4%) > Fe (39%). However, the concentrations of labile metals may pose no risk to the environment. In the column test, different rainwater conditions (i.e., natural rainwater and acidified rainwater) were used to imitate the leaching potential of the metals in the actual field. The pH of the soil primarily controlled metal migration into deeper layers. Cumulative metal concentrations in the leachates showed that Fe, Mn, and Cd were high in the tested soils but present at low concentrations, except for Cd. Cadmium showed a higher concentration than the WHO guideline for drinking water, and its seepage into deeper layers may affect the quality of groundwater.